Multicolor photometry of the classical nova V446 Her in "QUIESCENCE" - Pavlenko, E. P.; Mullanurova, D. N.; Baklanov, A. V.; Antoniuk, O. I.; Filatova, T. M. (Одеські астрономічні публікації, 2017)
We present the result of 2-year observations of Nova Her 1960 = V446 Her in 2002 - 2003. Data obtained in VRI spectral bands display the dwarf- nova-like outbursts with amplitude 1m - 1.8m and typical time of 14 days. The magnitude - color diagrams show the reddening with fainting. They support the idea that the nature of the outbursts could be the thermal instability in accretion disk around white dwarf.